Local Self-Government Financing and Costs of Municipality in Slovenia - Zan Jan OPLOTNIK; Bostjan BREZOVNIK; Borut VOJINOVIĆ (Transylvanian Review of Administrative Sciences, 2012)
This research paper focuses on the compliance of the actual system of financing local selfgovernment in Slovenia with the basic principles of the theory of decentralization and guidelines of the European Charter of Local Self-Government. It addresses the level of costs coverage within the municipal competence by using the allocated appropriate expenditure resources calculated according to the Law of Financing Municipality Act. The purpose of the paper is, therefore, to look for an answer to the question whether and to what extent the obtained funds correspond to the actual workload that municipalities have for performing statutory tasks and for exercising their competences. Analysis shows that, on an aggregate level, these actual systems ensure enough resources for local governments to cover their actual costs and current expenditures; some groups of municipalities, e.g. larger urban municipalities, municipalities with large proportions of elderly people etc. are faced with lack of funding, according to the actual costs data available, while other groups of municipalities receive more funds than they need.